2023
DOI: 10.1038/s41598-023-39059-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study on household air pollution exposure and prevalent chronic disease in the elderly

Abstract: Older people spend most of their time indoors. Limited evidence demonstrates that exposure to indoor air pollutants might be related to chronic complications. This study aimed to estimate the correlation between household air pollution (HAP)'s long-term exposure and the prevalence of elevated hypertension, diabetes mellitus (DM), obesity, and low-density lipoprotein (LDL) cholesterol. From the Global Burden disease dataset, we extracted HAP, hypertension, DM, body mass index, and LDL cholesterol data from Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Xu et al's study reported higher levels of TC, LDL-C, and ApoB in restaurant workers exposed to cooking fumes compared to control groups [49]. Dehghani et al reported that HAP exposure was associated with increased prevalence of high low-density lipoprotein cholesterol, high systolic blood pressure, and high body mass index, and diabetes mellitus-2 in the elderly [50]. However, the effect of indoor air pollution on blood lipids needs more research.…”
Section: Indoor Air Pollutionmentioning
confidence: 99%
“…Xu et al's study reported higher levels of TC, LDL-C, and ApoB in restaurant workers exposed to cooking fumes compared to control groups [49]. Dehghani et al reported that HAP exposure was associated with increased prevalence of high low-density lipoprotein cholesterol, high systolic blood pressure, and high body mass index, and diabetes mellitus-2 in the elderly [50]. However, the effect of indoor air pollution on blood lipids needs more research.…”
Section: Indoor Air Pollutionmentioning
confidence: 99%